2012
DOI: 10.1186/2041-7136-2-18
|View full text |Cite
|
Sign up to set email alerts
|

The economics and institutional economics of wildlife on private land in Africa

Abstract: doi:10.1186/2041-7136-2-18 Cite this article as: Child et al.: The economics and institutional economics of wildlife on private land in Africa. Pastoralism: Research, Policy and Practice 2012 2:18. Pgs.1-32Child et al. Pastoralism: Research, Policy and Practice 2012, 2:18 http://www.pastoralismjournal.com/content/2/1/18Publication of this article was funded in part by the University of Florida Open-Access publishing Fund. In addition, requestors receiving funding through the UFOAP project are expected to subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 23 publications
1
82
0
Order By: Relevance
“…To the contrary, however, role players within the sector believe that the transition to wildlife ranching has had a positive impact, namely, contributing toward overall economic growth, creating a number of skilled and semiskilled employment opportunities, as well as furnishing a source of foreign exchange, with these benefits spilling over to various recipients and sectors. These views are supported by the studies of Chardonnet et al (2002), Van der Merwe, Saayman and Krugell (2007), Musengezi (2010), Booth (2010), Saayman, Van der Merwe and Rossouw (2011a;2011b), and Child et al (2012), who revealed that the wildlife sector has the potential to contribute significantly toward economic growth and development. For example, results from a case study by Musengezi (2010), which included eight properties near the Kruger National Park, reveal that the financial returns of wildlife properties exceed those of extensive commercial beef production and provide a significant number of employment opportunities.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…To the contrary, however, role players within the sector believe that the transition to wildlife ranching has had a positive impact, namely, contributing toward overall economic growth, creating a number of skilled and semiskilled employment opportunities, as well as furnishing a source of foreign exchange, with these benefits spilling over to various recipients and sectors. These views are supported by the studies of Chardonnet et al (2002), Van der Merwe, Saayman and Krugell (2007), Musengezi (2010), Booth (2010), Saayman, Van der Merwe and Rossouw (2011a;2011b), and Child et al (2012), who revealed that the wildlife sector has the potential to contribute significantly toward economic growth and development. For example, results from a case study by Musengezi (2010), which included eight properties near the Kruger National Park, reveal that the financial returns of wildlife properties exceed those of extensive commercial beef production and provide a significant number of employment opportunities.…”
Section: Introductionsupporting
confidence: 66%
“…Analogous research by Van der Merwe et al (2007) and Saayman et al (2011a;2011b) not only discloses the significant contribution of the hunting industry toward real Gross Domestic Product (GDP) and employment, it also reveals noteworthy spill-over effects toward the rest of the economy. Moreover, PriceWaterhouse (1994), as well as Taylor (2002) and Langholz and Kerley (2006), as cited by Child et al (2012), conclude that wildlife enterprises not only create employment opportunities, but also more specialised employment opportunities, which increase wage bills some 20-to 32-fold. Nonetheless, these findings have not encumbered any of the controversies around the economic impact of the wildlife ranching sector.…”
Section: Introductionmentioning
confidence: 99%
“…Kenya's long-standing hunting and trade bans, strongly supported by international NGOs, have failed to prevent substantial wildlife losses and may have even facilitated them in the face of strong incentives to convert wildlife habitat to conventional agricultural uses (Norton-Griffiths 2010, Ogutu et al 2016). This stands in stark contrast with southern African countries that have employed the sustainable use approach: by enabling regulated and culturally appropriate commercial wildlife harvesting with meaningful benefits flowing to relevant local people, they have witnessed impressive expansion of managed wildlife habitats (Child et al 2012, Child andChild 2015).…”
Section: Resultsmentioning
confidence: 61%
“…Hoods of their community -stealing from the rich and redistributing back to the poor (Child, Musengez, Parent, & Child, 2012). It is possible that such a scenario was also present on these farms in Namibia.…”
Section: Discussionmentioning
confidence: 99%